2018
DOI: 10.1021/acsnano.8b01630
|View full text |Cite
|
Sign up to set email alerts
|

Digital Isotope Coding to Trace the Growth Process of Individual Single-Walled Carbon Nanotubes

Abstract: Single-walled carbon nanotubes (SWCNTs) are attracting increasing attention as an ideal material for high-performance electronics through the preparation of arrays of purely semiconducting SWCNTs. Despite significant progress in the controlled synthesis of SWCNTs, their growth mechanism remains unclear due to difficulties in analyzing the time-resolved growth of individual SWCNTs under practical growth conditions. Here we present a method for tracing the diverse growth profiles of individual SWCNTs by embeddin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 50 publications
5
37
0
Order By: Relevance
“…2 e). The measured heights of the CNTs fall within the typical diameter range of those on the growth substrates 29 . It is noteworthy that the anthracene stamp gives rise to only one tenth as much contamination as a PDMS stamp (Fig.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…2 e). The measured heights of the CNTs fall within the typical diameter range of those on the growth substrates 29 . It is noteworthy that the anthracene stamp gives rise to only one tenth as much contamination as a PDMS stamp (Fig.…”
Section: Resultssupporting
confidence: 56%
“…The improved transfer yield of the anthracene-assisted method may partially originate from the fact that 100% of the picked-up CNTs are released on the receiving substrates together with the anthracene crystals. We should note that the pick-up efficiency by the anthracene crystals is much higher for small diameter CNTs (~1 nm), but the diameter range of CNTs on quartz under the current growth condition (1.42 ± 0.17 nm 29 ) lies outside of the optimal range (Supplementary Fig. 3 ).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…[ 24,26,130 ] It was reported that any defects such as the pentagon‐heptagon pair in a SWCNT will change the local chirality. [ 131‐133 ] When disturbing the growth parameters during CVD, such as changing carbon feeding stocks [ 88,134 ] and introducing an electric field, [ 135 ] the as‐grown SWCNTs exhibited heterojunctions with different chiralities. With this strategy, the SWCNTs with high‐ purity electronic type [ 135 ] and specific chirality were obtained.…”
Section: Structure‐controlled Growth Of Carbon Nanotubes With Well‐defined Catalystsmentioning
confidence: 99%
“…1a). Several studies have captured the one-by-one growth rates by optical or electron microscopy [21][22][23][24], but the results often disagree with each other. Even for the case of alcohols as carbon sources [25], the discrepancy is evident.…”
Section: Introductionmentioning
confidence: 99%